1) (3/7 * 1/4) * (-4) = 3/7 * (1/4 * (-4)) = 3/7 * (-1) = -3/7;
ответ: -3/7.
2) (-4 1/5 * 1,3) * 10/13 = (-4 1/5 * 1 3/10) * 10/13 = (-21/5 * 13/10) * 10/13 = -21/5 * (13/10 * 10/3) = -21/5 * 1 = -21/5 = -4 1/5;
ответ: -4 1/5.
3) (-5 6/7 * 3/13) * (-4 1/3) = (-41/7 * 3/13) * (-13/3) = -41/7 * (3/13 * (-13/3)) = -41/7 * (-1) = 41/7 = 5 6/7;
ответ: 5 6/7.
4) -(7 5/12 + 7/36) * 5 1/7 = -(89/12 + 7/36) * 36/7 = -89/12 * 36/7 - 7/36 * 36/7 = -89/12 * 36/7 - 1 = -267/7 - 1 = -267/7 - 7/7 = -274/7 = -39 1/7.
ответ: -39 1/7.
Пошаговое объяснение: 4 567 × 6 = 27 402.
6 788 : 2 = 3 394
27 402 + 3 394= 30 796.
15 676 - 30 796 = -15 102